Mandibular bone mineral density variation in three West African Cercopithecoid monkey species: Associations with diet and feeding behavior. Issue 12 (December 2015) - Ray, Tyrun J.; McGraw, W. Scott; Sun, Zongyang; Jeon, Minjeong; Johnson, Trent; Cheffins, Katherine; Daegling, David J.; Kim, Do-Gyoon
Highlights: AB had lower but more heterogeneous distribution of mineral content than CB. AB and CB mineral content in the M2 region were higher than that of the I1 region. Cercocebus atys had higher CB mineral at the M2 region than did Colobus polykomos and Procolobus badius . C. atys is adapted for exploiting hard foods requiring high bite forces. Abstract: Objective: Procolobus badius, Colobus polykomos, and Cercocebus atys are three West African primate species known to have distinctive feeding behaviors. Our objectives were (1) to test whether intra-taxon variation in bone mineral content exists between anterior and posterior regions of the mandible and (2) to determine if interspecific differences are interpretable via feeding and dietary idiosyncracies among the three taxa. Design: Twenty-one mandibles from naturally deceased C. polykomos ( n  = 7), P. badius ( n  = 9), and C. atys ( n  = 5) were scanned using cone beam computerized tomography. Alveolar bone (AB) and basal cortical bone (CB) of incisor (I1 ) and second molar (M2 ) regions were digitally isolated. Degree of bone mineralization (DBM) distribution was obtained using histograms of CT attenuation values. Mean, standard deviation (SD), the 5th (Low5 ) and the 95th (High5 ) percentiles of the DBM histogram were compared between the jaw regions in species. Results: The mean and Low5 of DBM were significantly lower for AB than CB of all species ( p  < 0.001). The AB DBM parameters were not significantly different between I1 and M2 of all species ( p  > 0.056) except the mean of C. polykomos ( p  < 0.05). The mean, SD, High5 of CB DBM at M2 of C. atys was significantly higher than those of C. polykomos and P. badius ( p  < 0.006). Conclusions: The durophagous C. atys had higher CB DBM value at the M2 region than C. polykomos and P. badius, which supports the hypothesis that materially stiffer mandibular bone in C. atys can develop in response to the generation of high bite forces during hard object feeding.